Development of "petualangan matematika" learning media using scratch on probability material - Hatimah Hatimah; Soraya Djamilah; Arif Ganda Nugroho (Hipotenusa Journal of Research Mathematics Education (HJRME), 2026)
Mathematics, especially the topic of probability, is often considered abstract, complicated, and boring by students, which leads to low interest in learning. This condition is exacerbated by the use of monotonous conventional teaching methods. This study aims to: (1) provide an overview of the feasibility of developing an educational game titled “Petualangan Matematika” based on smartphones using the Scratch platform for the topic of Probability, (2) explain the validity of the educational game as assessed by expert validators, and (3) describe the practicality of the smartphone-based educational game in supporting the learning process of mathematics, specifically on the topic of Probability. The research employed the Research and Development (R&D) method by adopting the ADDIE development model, which consists of five systematic stages: Analysis, Design, Development, Implementation, and Evaluation. The visual design of the game was created using Canva, while the development of the educational game itself was carried out using the Scratch platform. The final product is an educational game that can be accessed and played on smartphone devices. The research subjects consisted of 27 students, divided into two groups: a small group of 5 students who participated in the readability test, and a larger group of 22 students who took part in the practicality test. The instruments used to assess both validity and practicality were questionnaires utilizing a Likert scale. The data analysis techniques involved evaluating the results of the readability and practicality tests. The results of the study concluded that: (1) the product, a smartphone-based educational game titled “Petualangan Matematika” for the topic of Probability, is categorized as highly feasible for use in learning activities; (2) the validity level of the game is very high, as evidenced by expert assessments: media expert validation yielded a score of 81.25%, while two subject matter experts provided scores of 93.75% and 100%, respectively; and (3) the game demonstrated a very high level of practicality, indicated by a 92% score in the readability test conducted with the small group and a 97.125% score in the practicality test with the larger group.